Numerical Simulation Analysis of an Offshore Multi-Row Arrangement Longline Aquaculture Facility with Lantern Nets Under Environmental Loads - Yingna Mu; Guoxuan Liang; Changping Chen; Ruitong Zhang; Fei Teng; Yanbin Tan (Fishes)
The structural hydrodynamic response of longline aquaculture facilities under the influence of waves and currents is complex. Studying the hydrodynamic characteristics of this aquaculture structure in complex sea environments can contribute to sustainable offshore aquaculture solutions. Thus, we established a numerical model using AquaSim2.18, a proven and effective finite element hydrodynamic software for analyzing the maximum tension in mooring lines and main lines, the displacement of the main lines, and the forces on the lantern nets under waves and currents. The results showed that positioning the system in the direction of incidence of waves and currents minimizes tension in both mooring and main lines, making a downstream arrangement optimal; compared with a single row, the maximum reduction in the tension of the mooring lines is 3.3% and 1.8% for five-row and row-row lines, respectively, and the shadow effects reduced the downstream mooring force. Additionally, line tension increased with wave height and current velocity, whereas wave periods had variable effects due to the period range; the lantern net forces increased with wave height and decreased with wave period. Wave height was also shown to influence the horizontal displacement of main lines. The findings can provide a reference for the hydrodynamic characteristics of different components of the structure.